Peranan Sales Promotion Girl Pada Produk Wardah Beauty Care - Pinto Jaya; Yuwanda Tiara; Mumuh Mulyana (Program Vokasi dan LPPM IBI Kesatuan, 2022)
ABSTRACT At present the cosmetics industry in Indonesia has increased by 20% in 2017, so competition in the cosmetic industry is quite tight. There are many ways that companies can do in marketing their products, namely through personal selling, in personal selling it is certain that it requires workers to carry out these activities, one of which is by using a Sales Promotion Girl. The aims of this research are: 1). To find out how the role of Sales Promotion Girl is in wardah beauty care products. 2). To know how the Sales Promotion Girl in promoting the product. 3). To find out how Sales Promotion Girl can attract and convince consumers. The results of this study, namely: 1). The role of the Sales Promotion Girl in wardah beauty care products is as follows: a) attracting consumers to visit the stand, b) offering products, c) guessing customer needs and fulfilling what customers need, d) answering customer questions and handling complaints from customers in a timely manner well, e) informing the quality of the product up to the way it is treated or used, and f) implementing service standards properly. 2). When Wardah's Sales Promotion Girl promotes products, namely by: a) product presentations, and b) promotional presentations. 3). The Sales Promotion Girl's way of attracting and convincing consumer interest is by: a) good appearance according to company standards, b) product display, c) product presentation, and d) with promotions.